APPLICATION OF MANUAL THERAPY IN MUSCLE TENSIONAL DYSPHONIA - Jovanovic, Stevan; Stojanovic-Jovanovic, Biljana; Kljajic, Dragana; Arsic, Sladjana; Trajkov, Marija (PONS - medicinski časopis, 2021)
Introduction: Muscle tension dysphonia is a functional voice disorder caused by unbalanced activity of the laryngeal and extralaryngeal muscles. People with dysphonia may have changes in the cervical and perilaryngeal muscles, limited amplitude of movement of the cervical spine, but also posture disorders. The aim of this paper is to present the analyzed therapeutic effects of manual techniques in muscule tension dysphonia, based on a review of the available literature. Method: In accordance with the set criteria and the goal of the paper, the collection and analysis of professional and scientific research papers available in PubMed / MEDLINE databases, published in the period from 2004 to 2018, was performed. The analyzed studies belong to the type of clinical studies and by design, two types of studies are included: the type of randomized control study and the study of one group of subjects with pre- and post-examination (ex-post factor). Some studies with one group of respondents were characterized by the authors as a series of cases and one, as a small pilot study of repeated measures. The results of the research indicate a larger number of corrective effects of laryngeal manual therapy. It is certain, that by developing a broader manual-therapeutic approach, the etiological factor of muscle tension dysphonia can be more effectively influenced. That approach, leads to a reduction in pain, improvement of physical functioning as well as improvement of specific vocal qualities.